Extreme precipitation-based vulnerability assessment of road-crossing drainage structures in forested watersheds using an integrated environmental modeling approach. (September 2022) - Panda, S.S.; Amatya, D.M.; Grace, J.M.; Caldwell, P.; Marion, D.A.
Abstract: The goal of this study is to develop geospatial-hydrology models incorporating design rainfall intensities and land morphologic features to identify erosion hazards and vulnerability risks to road culverts/stream crossings in three watersheds at USDA Forest Service long-term experimental forests: i) Coweeta Hydrologic Laboratory, NC, ii) Santee Experimental Forest, SC, and iii) Alum Creek Experimental Forest, AR. These models developed in an ArcGIS ModelBuilder platform were: i) Streambank Erosion Vulnerability Assessment (SBEVA) and ii) Modified Revised Universal Soil Loss Equation (MODIFIED-RUSLE) for potential erosion and streambank vulnerability estimation. The SBEVA model, developed using a Delphi-based weighted-probability scale, and MODIFIED-RUSLE were integrated to identify locations of culverts/stream-crossings morphologically vulnerable to erosion and scouring, which were ground-truthed for the SC site only. As the MODIFIED-RUSLE model does not assess streambank erosion, its integration with the SBEVA helps to develop a better decision-support tool for relevant agencies for safeguarding these road culverts/stream crossings.